Management of autism and attention-deficit hyperactivity disorder in Dup15q syndrome - Gudipati, Pranati; Suthar, Himani; Narravula, Rithika; Patel, Dhruvin; Parikh, Parinda (International Journal of Research in Medical Sciences, 2026)
Dup15q syndrome is an uncommon neurogenetic disorder caused by duplications of chromosome 15q11.2-13.1, typically through idic (15) or interstitial duplications. Its prevalence is about 1 in 5,000 births and is characterised by hypotonia, developmental delays, intellectual disability, autism, and seizures, with greater severity in maternally derived duplications. Symptoms overlap with related conditions such as Prader-Willi and Angelman syndromes. Early detection and intervention, supported by a robust database, will improve quality of life. An 11-year-old girl with Dup15q syndrome was referred for psychiatric evaluation due to her emotional and behavioral issues at school. She had a history of developmental delays and persistent autistic traits. Her parents noted early morning awakenings and negative self-talk. At the time of evaluation, she was receiving psychotropic and antiepileptic medications. The review found her restless and tense, with limited insight. To ensure her safety, the school provided one-on-one support during medication adjustments, and she showed some improvement in the following weeks. However, she still faced challenges with sensory dysregulation and emotional reactions. Dup15q syndrome is a complex neurogenetic disorder that requires early detection and intervention for optimal outcomes with genetic testing and personalized care strategies. Addressing the behavioral, social, and sensory challenges associated with the condition is essential, as these difficulties will intensify with age. Ongoing research and the development of support networks are vital to enhancing the quality of life for individuals with Dup15q syndrome and their families.